Canadian Geoscience Diplomacy in Collaboration with IUGS, UNESCO IGCP Geoparks, and World Heritage Geosites: Past, Present, and Future - Bingham-Koslowski, Nikole; Boggs, Katherine J.E.; Adiyaman Lopes, Özlem; Lebel, Daniel; Johnston, Stephen; Narbonne, Guy (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2023)
To commemorate the 60th anniversary of IUGS and the 50th anniversary of IGCP, the 2022 symposium entitled “IUGS, Geoparks, and IGCP – Retrospection, today and the future” was coordinated at the GAC-MAC-IAH-CNC-CSPG 2022 Conference in Halifax (16–18 May) with the companion Cliffs of Fundy UNESCO Geopark field trip (19–21 May). Canadian leadership within IUGS and IGCP includes J.M. Harrison as the first president of IUGS in 1961, Antony Berger’s work publishing “Episodes”, which is the IUGS’ quarterly international scientific journal, and Canadian leadership on multiple IGCP projects summarized here. Two panel discussions examined the future of geosciences, UNESCO Geoparks and World Geoheritage Sites in Canada. The need for improved communications with politicians, policymakers, and the general public through education and outreach was emphasized in these panel discussions. UNESCO Geoparks (such as the Cliffs of Fundy), UNESCO World Heritage Geosites and significant museum displays represent vehicles for improving communications with the general public about geosciences and potentially inspiring future geoscientists. This report provides a summary of the symposium and explores some of the many themes that it addressed.